Manajemen Pemasaran Pendidikan Berbasis Kearifan Lokal: Upaya Peningkatan Kuantitas Santri di Era 4.0 - Rofiki, Moh.; Afifatur Rahmah; Nadiatur Rohmah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to analyze marketing strategies that combine local cultural values with digital technology and the challenges faced. A qualitative approach with a case study type was used in the research. The data collection techniques used include participant observation, in-depth interviews, and documentation. The results showed that the integration of local wisdom in marketing helped strengthen the pesantren's identity and attract prospective students, while the adoption of digital communication technologies such as e- learning and social media successfully expanded the marketing reach and increased the accessibility of education. However, the research also identified challenges such as limited technological infrastructure and the need for adequate training. Recommendations include increased investment in technology infrastructure, continuous training for staff and santri, and the development of a balanced marketing strategy between local values and technology. The results of this study are expected to provide insights for other educational institutions in adopting similar approaches to improve the quality of education and the attractiveness of institutions in the digital era.